Determinants of penetrance and variable expressivity in monogenic metabolic conditions across 77,184 exomes - Julia K. Goodrich (Nature Portfolio, 2021)
Penetrance of variants in monogenic disease and clinical utility of common polygenic variation has not been well explored on a large-scale. Here, the authors use exome sequencing data from 77,184 individuals to generate penetrance estimates and assess the utility of polygenic variation in risk prediction of monogenic variants.